Effects of Pruning, Branch Bending, and Biofertilizer Application on Flowering and Fruiting of Guava “Crystal” - Natalia, Cristina Evi; Susanto, Slamet; Suketi, Ketty; Hapsari, Dhika Prita (Department of Agronomy and Horticulture, IPB University, 2025)
Guava “Crystal” is one of Indonesia’s most popular varieties; its demand continues to increase, so it is important to examine methods to increase fruit production. This research aims to increase the flowering and fruiting of guava “Crystal” through branch-bending and application of biofertilizer. The results showed that pruning + bending significantly increased the number of shoots by 15.8%, shoot length by 11.16%, and leaf number by 15.09%. This treatment also increased flower number by 88.84%, fruit number by 77.9%, and double the fruit weight. Biofertilizers significantly increased vegetative growth in the form of the number of shoots (5.12%), shoot length (9.21%), and number of leaves (10.29%). Pruning + bending and biofertilizer did not significantly affect weight per fruit, fruit diameter, fruit volume, fruit firmness, total soluble solids, total titratable acids, and vitamin C content.